Threshold effects in the US budget deficit - Philip Arestis; Andrea Cipollini; Bassam Fattouh (Levy Economics Institute of Bard College, 2002)
We contribute to the debate on whether the large U.S. federal budget deficits are sustainable in the long run. We model the U.S. government deficit per capita as a threshold autoregressive process. We find evidence that the U.S. budget deficit is sustainable in the long run and that economic policymakers will intervene to reduce per capita deficit only when it reaches a certain threshold.
Keywords: 330